The Effect of Ascorbic Acid Treatment on Viability and Vigor Maize (Zea mays L.) Seedling under Drought Stress - HAMIDAH HAMAMA; ENDANG MURNIATI (Bogor Agricultural University, Indonesia, 2010)
This study was conducted in the laboratory and the field to examine the effects of ascorbic acid treatment on germination and seedling growth under drought stress. The laboratory works consisted of two experiments and were designed to determine the critical osmotic potential of maize and to determine the optimum ascorbic acid concentration. The field study was designed to examine the effects of soaking seed in ascorbic acid on seedling growth under drought stress. Drought condition was simulated by PEG-6000 and regulation of water treatment. During the first experiment, interactions of both osmotic potential and varieties were significant at all variables. Germination percentage and speed of germination were significantly decreased by increasing of osmotic potential. The second experiment showed that interactions of both factors were significant at all variables except vigor index, the length of shoot, primary, and seminal root. The results showed that the ascorbic acid treatment improved the germination percentage, the speed of germination and the vigor index compared with the control, besides the increase in length of shoot, primary and seminal root and number of seminal root. However, the best result was showed by 55 mM ascorbic acid. The result of field experiment showed that interactions were not always significant and 55 mM ascorbic acid treatment increased the seedling height, the number of leaves and leaf area but it had no effect on the water deficit and the root length.